PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR AGAMA ISLAM KELAS VB SD NEGERI 37 PEKANBARU - Islamiyah Islamiyah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The application of this guided incuri learning model was applied to VB grade 37 Pekanbaru Elementary School students, because conventional learning or using the lecture method did not work. The purpose of the study was to improve the learning outcomes of Islamic Education in disciplinary material and to help VB grade 37 Pekanbaru Elementary School students. The research subjects were 32 students of VB class consisting of 18 men and 16 women and carried out in 2 cycles. Analysis of the results of actions, namely student activities, teacher activities through observations. The activities of students and teachers at each meeting always increase. Student learning completeness also increased. Before action was taken, students who completed only 15 people (44.12%) with an average score of 70.75. After the first cycle of action was taken, students who completed it increased to 28 people (82.35%) with an average score of 77.75. and in the second cycle the number of students who completed increased to 33 people (97.05%) with an average value of 85.00. Based on the results and discussion, the implementation of the guided inkuri learning model can improve the learning outcomes of PAI students in class VB Pekanbaru Elementary School 37. One student who does not complete learning will be given remedial instruction.